1988
DOI: 10.1080/07300077.1988.11878791
|View full text |Cite
|
Sign up to set email alerts
|

High Blood Pressure Induced by Audiovisual Stimulation in Young Rats: Effect of Antihypertensive Agents

Abstract: High systolic blood pressure (BP) was induced in young Wistar rats by daily exposure for 30 mins to environmental stimuli consisting of intense (100 dB) sound of 7500 cps and flashing light (0.3 cps). Maximal BP enhancement was obtained after the application of both these stimuli for 3 consecutive days. Such a hypertensive response was detected 24 hrs, but not 1 hr after the trial. High BP backed to normal 72 hrs after discontinuation of the audiovisual stimulation trials. Clinically effective antihypertensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Indeed, the authors reported that suppression of the pituitary adrenocorticotropic hormone (ACTH) response to stress blocked the interference following OFL presentation, suggesting that this interference was partly due to the release of ACTH (Netto et al 1991). Stimulation with flashing lights is typically used within chronic stress paradigms (Gamaro et al 2003;Grippo et al 2003), and has been shown to induce high blood pressure when paired with an intense sound (Florentino et al 1988). As previously said, the events we used to modulate spatial memory did not include aversive stimuli.…”
Section: Behavioral Interpretationmentioning
confidence: 86%
“…Indeed, the authors reported that suppression of the pituitary adrenocorticotropic hormone (ACTH) response to stress blocked the interference following OFL presentation, suggesting that this interference was partly due to the release of ACTH (Netto et al 1991). Stimulation with flashing lights is typically used within chronic stress paradigms (Gamaro et al 2003;Grippo et al 2003), and has been shown to induce high blood pressure when paired with an intense sound (Florentino et al 1988). As previously said, the events we used to modulate spatial memory did not include aversive stimuli.…”
Section: Behavioral Interpretationmentioning
confidence: 86%
“…Cicletanine was also tested in rats made hypertensive by isolation or by audiovisual stimulation. The drug was effective at single oral doses of 10 and 30 mg/ kg ( 10 ).…”
Section: P E Chabrier Et Almentioning
confidence: 98%
“…- 10 i, 10 20 lar reactivity to vasoconstrictor substances, demonstrable even in the prehypertensive state. The effects of 2 weeks of oral treatment with cicletanine (0.3-300 mg/ kg) on the onset of hypertension in SH-SP rats on high salt diets were compared with those of four other antihypertensive drugs: prazosin, an a-blocker (3-30 mg/kg), captopril, an inhibitor of angiotensin-converting enzyme (0.3-300 mg/kg), indapamide (0.1-0.3 mgkg), and hydrochlorothiazide (1-10 mg/kg), diuretics (22).…”
Section: P E Chabrier Et Almentioning
confidence: 99%
“…For example, in one study mice were exposed to sound for 24 h (Yu et al, 2005), in another study rats were maintained in visually stimulating environment for 8 h (Bissig and Berkowitz, 2009). Such long periods of passive (and unavoidable) exposure to sensory stimulation may produce nonphysiological patterns of activations reflecting not only the prolonged stimulation but also stress responses (Florentino et al, 1988;Geber, 1966;Hartel and Hartel, 1960). In the present study, we tested rat voluntary behavior; the amount of running activity was not restricted by the experimenter, which makes, in our opinion, this experimental situation physiologically more natural.…”
Section: Application Of Memri For Whole-brain Mapping In Behaving Animentioning
confidence: 99%